Dynamic state of plasmid genomic architectures resulting from XerC/D-mediated site-specific recombination in Acinetobacter baumannii Rep_3 superfamily resistance plasmids carrying blaOXA-58- and TnaphA6-resistance modules - Giacone, Lucía; Cameranesi, M. Marcela; Sanchez, Rocío I.; Limansky, Adriana S.; Morán-Barrio, Jorgelina; Viale, Alejandro M. (Frontiers in Microbiology, 2023)
The acquisition of blaOXA genes encoding different carbapenem-hydrolyzing class-D β-lactamases (CHDL) represents a main determinant of carbapenem resistance in the nosocomial pathogen Acinetobacter baumannii. The blaOXA-58 gene, in particular, is generally embedded in similar resistance modules (RM) carried by plasmids unique to the Acinetobacter genus lacking self-transferability. The ample variations in the immediate genomic contexts in which blaOXA-58-containing RMs are inserted among these plasmids, and the almost invariable presence at their borders of multiple non-identical 28-bp sequences potentially recognized by the host XerC and XerD tyrosine recombinases (pXerC/D-like sites), suggested an involvement of these sites in the lateral mobilization of the gene structures they encircle. However, whether and how these pXerC/D sites participate in this process is only beginning to be understood. Here, we used a series of experimental approaches to analyze the contribution of pXerC/D-mediated recombination to the generation of structural diversity between resistance plasmids carrying pXerC/D-bounded blaOXA-58- and TnaphA6-containing RM harbored by two phylogenetically- and epidemiologically-closely related A. baumannii strains of our collection, Ab242 and Ab825, during adaptation to the hospital environment. Our analysis disclosed the existence of different bona fide pairs of recombinationally-active pXerC/D sites in these plasmids, some mediating reversible intramolecular inversions and others reversible plasmid fusions/resolutions. All of the identified recombinationally-active pairs shared identical GGTGTA sequences at the cr spacer separating the XerC- and XerD-binding regions. In addition, the fusion of two Ab825 plasmids mediated by a pair of pXerC/D sites displaying sequence differences at the cr spacer could be inferred on the basis of sequence comparison analysis, but no evidence of reversibility could be obtained.